Parental SES and Students’ Efficacy in English Learning - Wulandari, Dyah Peni; AM, Mukhlisah (ICONELT, 2022)
This study reviews a selected sample of 22 research articles on parental SES and students’ efficacy in English learning, this study was using content analysis of the published articles between 2010 and 2020. This study found that those three variables were separately studied in the past time. Furthermore, the factors beyond them such as parental income (SES), social persuasion and mastery experiences (Self-efficacy) in English learning may be possible correlation of those three variables.